New determination of double-β-decay properties in 48Ca: high-precision Qββ-value measurement and improved nuclear matrix element calculations - Kwiatkowski, Anna; Brunner, Thomas; Holt, J. D.; Chaudhuri, A.; Chowdhury, U.; Eibach, M.; Engel, J.; Gallant, Aaron; Grossheim, A.; Horoi, M.; Lennarz, A.; Macdonald, T. D.; et al. (Physical review. C, Nuclear physics, 2014)
We report a direct measurement of the Qββ value of the neutrinoless double-β-decay candidate 48Ca at the TITAN Penning-trap mass spectrometer, with the result that Qββ=4267.98(32)keV. We measured the masses of both the mother and daughter nuclides, and in the latter case found a 1 keV deviation from the literature value. In addition to the Qββ value, we also present results of a new calculation of the neutrinoless double-β-decay nuclear matrix element of 48Ca. Using diagrammatic many-body perturbation theory to second order to account for physics outside the valence space, we constructed an effective shell-model double-β-decay operator, which increased the nuclear matrix element by about 75% compared with that produced by the bare operator. The new Qββ value and matrix element strengthen the case for a 48Ca double-β-decay experiment.
Im Titel ist die Zahl 48 hochgestellt, die Zeichen ββ sind tiefgestellt
Gesehen am 04.09.2020